Updates on Selective Brain Hypothermia: Studies From Bench Work to Clinical Trials - Wang, Xiaoyu; Wehbe, Alexandra; Kaura, Shawn; Chaudhry, Naveed; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2022)
Thrombectomy or thrombolysis are the current standards of care for acute ischemic stroke (AIS), however, due to time constraints regarding operations and a multitude of contraindications, AIS remains one of the leading causes of death and chronic disability worldwide. In recent years, therapeutic hypothermia has been explored as an adjuvant therapy for AIS treatment and has shown potential to improve outcomes in patients with AIS. In particular, selective therapeutic hypothermia has shown to markedly reduce infarct volumes and have neuroprotective effects, while also minimizing many systemic side effects seen with systemic therapeutic hypothermia. Both preclinical and clinical trials have demonstrated that selective therapeutic hypothermia is a safe and feasible therapy for patients who have suffered an AIS. In this review, we summarize the current update on selective hypothermia through major studies that have been conducted in rodents, large animals, and clinical trials, and briefly discuss the prospects of selective hypothermic research. We hope this review helps facilitate the exploration of other possible adjuvant treatment modalities in the neuroprotection of ischemic stroke, whether upon symptom onset or after vascular recanalization.